Perbandingan Kinerja Reksa Dana Saham dan Campuran dengan Metode Sharpe, Treynor, Jensen, Information, dan Sortino Ratio (2021-2023) - Sutjipto, Nathanael; Mindosa, Bonnie (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The significant growth of mutual fund investors underscores the importance of meticulous fund selection based on performance. This study compares the performance of equity and balanced funds using various metrics including Sharpe, Treynor, Jensen's Alpha, Information, and Sortino ratios to determine their relative strengths. Conducted as a case study, the research delves into the performance analysis of these fund types. Findings reveal that equity funds outperform in Sharpe, Treynor, and Sortino ratios, while balanced funds exhibit superiority in Jensen's Alpha and Information ratios despite their overall negative performance. The study highlights the advantages of balanced funds according to their higher number of products generating positive returns and outperforming the IHSG. However, equity funds demonstrate superiority in certain measurement methods. The importance of careful fund selection for investors is emphasized, urging consideration of historical performance and measurement methods aligned with their investment objectives. This research contributes to informing investors' decisions in navigating the mutual fund market.